Peningkatan Hasil Belajar Siswa dalam Menyelesaian Soal-Soal Materi SPLDV Melalui Implementasi Pembelajaran Kooperatif Tutor Sebaya Bagi Siswa Kelas VI SDN 178 Pinrang - Ekajayanti Putri, Julia Ananda; Syawaluddin, Ahmad; Andriany, Mega (Universitas Negeri Makassar, 2025)
In the learning of Two Variable Linear Equation System System (SPLDV) Mathematics students of 6th grade of Primary School Negeri 178 Pinrang are still many who are under KKM (KKM 65) especially in solving problems. Therefore, it is necessary to make an effort to improve the results of Mathematics learning, namely through the implementation of cooperative learning with peer tutors. This study aims to determine the improvement of learning outcomes of 6th grade students of SDN 178 Pinrang in the 2023/2024 academic year in completing questions on the subject matter of SPLDV through the implementation of cooperative learning with peer tutors. The subjects of the study were class VI students of SDN 187 Pinrang number 28 children, a Math teacher and an observer. The data collected include student learning outcomes, teacher observation results, student observation results. This study is a Class Action Research (PTK) conducted in two cycles. Each cycle consists of 4 (four) stages: planning, execution of action, observation and reflection. In this study, it was said to be successful if at least 85% of students obtained grades ≥ 65. The results showed: (1) Students' learning obedience in cycle I was 62.50% with an average score of 67.13 and in cycle II of 87.50% with an average score of 77.88 (2) Student activity score in cycle I was 70% and in cycle II was 82.50%. From the above data it is clear that in cycle I learning outcomes are not as expected which means success indicators have not been met while in cycle II learning outcomes have been as expected which means success indicators have been achieved.